TEACHING A FOREIGN LANGUAGE USING INTERACTIVE TEACHING METHODS IN INSTITUTIONS EDUCATION OF THE I-II LEVEL OF ACCREDITATION (Pedagogy of Higher and Secondary Education, 2008)
In article to be considered effectiveness of using interactive methods of studying in the process of learnin foreign languages in higher educational of 1-11 degrees of accreditation.